In vitro screening of systemic fungicides against Phytophthora causing abnormal leaf fall disease of rubber (Hevea brasiliensis) trees - Roy C.B; Coffey M.D; Jacob C.K; Prem E; Premraj P (Fifth IUFRO Phytophthoras in Forests and Natural Ecosystems, 7-12 March 2010, Auckland and Rotorua, New Zealand, Abstract, p. 36.)
Abnormal leaf fall (ALF) disease caused by Phytophthora spp is an annually recurring destructing disease of rubber trees in India causing significant loss to rubber production. Copper oxychloride (COC) in mineral oil (as low volume spraying) and 1;Bordeaux mixture (as high volume spraying) are extensively used for the management of this disease. With an aim of devising possible better strategies for controlling Phytophthora, some preliminary studies using systemic fungicides were undertaken. Effectiveness of five systemic fungicides [Aliette (Fosetyl-A1), Ridomil (Mancozeb + Metalaxyl), KPHITE 7LP (Mono and di-potassium salts of Phosphorous acid), Calixin (Tridemorph) and Tilt (Propiconazole)] along with one contact fungicide Fytran (COC) was tested in the laboratory for their efficacy against Phytophthora following standard techniques. Ridomil, KPHITE 7LP and Aliette inhibited hyphal growth in fungicide amended media (poisoned food technique) at 20, 400 and 1250 ppm respectively. These three fungicides also inhibited sporangia formation and zoospore germination at 100 ppm and thus appeared to be effective in curtailing growth of Phytophthora in vitro. Leaf disc assay performed in vitro by inoculating leaf discs with Phytophthora and floating them in test fungicide solutions revealed Ridomil and KPHITE 7LP were most effective in inhibiting Phytophthora while COC was less effective. Acropetal transport of the systemic fungicides was noted with Aliette, Ridomil and and KPHITE 7LP in an assay using excised shoots from two clones: RRII 105 (relatively tolerant clone) and RRIM 600 (susceptible clone), dipped in the fungicide solution and inoculated with Phytophthora as no necrosis was observed. Studies to ascertain the protective and curative role of these fungicides revealed KPHITE 7LP. Aliette and Ridomil were effective as protective treatment, whereas KPHITE 7LP alone was efficient as curative treatment. Since Phytophthora survives in the soil and litter present in the floor of rubber plantation during unfavourable climatic conditions, an experiment was designed by providing artificial inoculum in known quantity of sterilized soil and drenching the soil with these fungicides. Growth of Phytophthora was completely inhibited when the soil was drenched with KPHITE 7LP and not with any of the other test fungicides. The results obtained from the present preliminary studies indicate that the systemic fungicides KPHITE 7LP, Ridomil and Aliette are equally effective against Phytophthora causing leaf disease in rubber. However, this study is being extended to the glass house condition followed by field-testing to arrive at a conclusion about the possibility of using these systemic fungicides in the control of Phytophthora on rubber trees.
Keywords: Abnormal leaf fall; Disease control; Phytophthora